Effect of Cleaning Process of Substrate on the Efficiency of the DSSC. Issue 1 (2nd January 2016) - More, Venumadhav; Shivade, Vivek; Bhargava, Parag
ABSTRACT: Cleaning of the FTO substrate is being done to remove the debris present on the substrate during the fabrication of dye sensitized solar cells (DSSC's). Sonication of FTO substrates by keeping it in soap solution, ethanol and distilled water followed by drying at 100°C has been reported by researchers. Some researchers have mentioned the use of ultr aviolet ozonization (UV-O3 ) processes to remove the organic contamination over FTO substrates. The present work shows the effect of cleaning of the FTO substrates on efficiency of the DSSC. Cleaning of FTOs was done by two methods – one by only bath sonication and other by bath sonication followed by heat treatment. It was found that heat treatment effectively removed organics compared to the non heat treated process. Heat treatment improved the performance of DSSC's by enhancing the adhesion of titania film to the FTO substrate. GRAPHICAL ABSTRACT: